Major gastrointestinal bleeding often is caused by occult malignancy in patients receiving warfarin or dabigatran to prevent stroke and systemic embolism from atrial fibrillation - Flack, Kathryn F.; Brückmann, Martina (Clinical gastroenterology and hepatology, 2017)
Background & Aims: Gastrointestinal (GI) bleeding in patients receiving anticoagulation agents can be caused by occult malignancies. We investigated the proportions and features of major GI bleeding (MGIB) events related to occult GI cancers in patients receiving anticoagulation therapy. Methods: We analyzed data from the Randomized Evaluation of Long Term Anticoagulant Therapy study (conducted between December 2005 and March 2009 in 951 clinical centers in 44 countries worldwide), which compared the abilities of dabigatran vs warfarin to prevent stroke and systemic embolism in 18,113 patients with atrial fibrillation. Two blinded gastroenterologists independently reviewed source documents of MGIB events (n = 595) that occurred during the study period. We collected data on MGIB events caused by previously unidentified GI malignancies, and compared characteristics of MGIB events in patients who received dabigatran vs warfarin (primary end point), and in patients with bleeding from cancer, vs patients bleeding from a nonmalignant or unidentified source. Results: Of 546 unique MGIB events, 44 (8.1%) were found to be from GI cancers (34 of 398 MGIB events in dabigatran users and 10 of 148 MGIB events in warfarin users; P = .60). Colorectal cancer accounted for 35 of 44 of all cancers identified. There were more colorectal cancer-associated MGIB events in the dabigatran group (30 of 34) than in the warfarin group (5 of 10) (P = .02), but more gastric cancer-associated MGIB events in the warfarin group (5 of 10) than in the dabigatran group (1 of 34) (P = .001). There were no differences in the short-term outcomes of cancer-related MGIB events in the dabigatran vs the warfarin group, but 75% of all cancer-related MGIB events required at least 1 blood transfusion and the mean hospital stay was 10.1 days. Compared with MGIB events from a nonmalignant or unidentified source, MGIB from cancer occurred sooner (343.0 vs 223.1 d; P = .003), but the bleeding was more likely to be chronic (for >7 d) (27.3% vs 63.6%; P < .001). Conclusions: In evaluating data from a study of the effects of anticoagulation therapy, we found approximately 1 of every 12 MGIB events to be related to an occult cancer. Approximately two thirds of cancer-related MGIB presents with chronic bleeding, and morbidity, and resource utilization is high.
Gesehen am 21.08.2019
Available online 17 October 2016